Strategy to Increase Talent Retention by Using Gamification and a Holistic Approach in Increasing Talent Retention and Employee Engagement: A Systematic Literature Review - Yuhelmis; Tukiran, Martinus; Yusnita, Nancy; Sunaryo, Widodo; Hidayat, Yayan (IJOSMAS, 2024)
Employee retention is an important issue for organizations in various industries. The ability to retain skilled employees is critical to maintaining organizational performance, competitiveness, and sustainable growth. This systematic literature review aims to synthesize findings from various leading international journals to provide a comprehensive understanding of the factors that influence employee retention and the strategies that can be used to improve it. Talent is considered as the potential or ability of different individuals to implement organizational growth strategies and is a term that is widely discussed in the contemporary era. When handled well, talented human resources encourage organizational efforts to implement growth strategies thereby providing sustainability for the organization and encouraging economic growth. . This research uses Preferred Reporting Items for Systematic Reviews. Data was obtained from online databases, namely JSTOR, AOS-Strategi and Inovasi, John Wiley and Sons Inc, Emerald Publishing, Interscalene Publishers, SAGE Publications, University of Minnesota, Technical Publishing, Technical University of Liberec, Routledge. 65 articles were obtained. By using the keyword search